Lemmus lemmus - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Norwegian Lemming Lemmus lemmus (Linnaeus, 1758) Type locality: alpibus Lapponicus [Mountains of Lappmark, Sweden] (Linnaei, 1758). Synonyms: L. norvegicus Desmarest, 1822 [TL: Les montagnes de la Norwege et la Laponie suedoise <.> les montagnes de la Laponie russe] (Desmarest 1822; Wilson & Reeder 2005; Wilson et al. 2017); L. borealis Nilsson, 1829 [a replacement name for Mus lemmus Linnaeus, 1758] (Wilson & Reeder 2005; Wilson et al. 2017); Cuniculus iterator Gistel, 1850 [TL: Russian Lapland =Kola Peninsula, Russia] (Wilson & Reeder 2005; Wilson et al. 2017). Distribution: European mountain species with a disjunctive range: Fennoscandia (nominate subspecies) and Novaya Zemlya ( L. lemmus chernovi ssp. nov. ). Comments: The insular geographic race on Novaya Zemlya is isolated from the nominate subspecies by a 600 km wide marine barrier (Fig. 1A). Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on page 115, DOI:10.37828/em.2021.40.8, http://zenodo.org/record/13233031